2015
DOI: 10.1093/aob/mcu244
|View full text |Cite
|
Sign up to set email alerts
|

Are tetraploids more successful? Floral signals, reproductive success and floral isolation in mixed-ploidy populations of a terrestrial orchid

Abstract: The results suggest that floral isolation and increased reproductive success of polyploids may help to explain their successful persistence in mixed-ploidy populations. These factors might even initiate transformation of populations from pure diploid to pure tetraploid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 91 publications
3
40
0
Order By: Relevance
“…A range of phenotypic and genotypic effects might explain the relative success of polyploids (Van de Peer et al, 2017). It has been observed that polyploidy can have a direct influence on the plant phenotype, leading, for instance, to bigger flowers and/or increased stature (Chen, 2010;Gross and Schiestl, 2015), as well as on the plant genotype, leading to genomic rearrangements and gene expression changes (Adams and Wendel, 2005;Chen, 2007;Buggs et al, 2011;Chester et al, 2012;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A range of phenotypic and genotypic effects might explain the relative success of polyploids (Van de Peer et al, 2017). It has been observed that polyploidy can have a direct influence on the plant phenotype, leading, for instance, to bigger flowers and/or increased stature (Chen, 2010;Gross and Schiestl, 2015), as well as on the plant genotype, leading to genomic rearrangements and gene expression changes (Adams and Wendel, 2005;Chen, 2007;Buggs et al, 2011;Chester et al, 2012;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, new species face two challenges: (1) they must evolve reproductive isolation to prevent gene flow with closely related species; and (2) they must establish a unique niche, either through ecological divergence or successfully outcompeting other species (Coyne and Orr, ; Via, ; Barton, ). Because crosses between plants of different ploidy levels frequently result in reduced hybrid fertility (Husband and Schemske, ; Husband and Sabara, ; Sweigart et al., ; Borges et al., ; Greiner and Oberprieler, ; Gross and Schiestl, ; Roccaforte et al., ; Pegoraro et al., ; however, see Lafon‐Placette et al., ), it has been suggested that polyploidization causes instantaneous speciation (Schluter, , ; Rundle and Nosil, ). However, for a new polyploid lineage to become a new species, it must also overcome the challenge of establishing a self‐sustaining population.…”
mentioning
confidence: 99%
“…through niche differentiation; Karunarathne et al 2018). Ecological differentiation among cytotypes growing in sympatry or in zones of contact frequently involves a differentiation in flowering time, which reduces hybridization among cytotypes and thereby facilitates their coexistence (Thompson 1992;Gross and Schiestl 2015). These processes enhance speciation events and therefore contribute to increased local diversity.…”
Section: Discussionmentioning
confidence: 99%